How Short-Term Rentals are Changing the Neighborhood - Wrede, Matthias (International Regional Science Review, 2022)
This paper examines how short-term rentals are changing living conditions and the composition of the population in affected parts of a town. First, to analyze the relation between quality, distance, and rents, we develop a spatial monocentric city model with varying housing quality levels. Second, for 200 m grids in the city of Berlin (Germany) in 2019, we show that the proportion of low and medium quality residential units correlates positively near the city center with the probability of Airbnb listings and the number of these listings, but negatively in the suburbs. Third, applying fixed effect and IV strategies, we investigate the impact of Airbnb listings on living conditions and the composition of the population in the almost 450 planning areas of Berlin in the years 2016–2019. We show that Airbnb offers increase the number of residents with long periods of residence and reduce the number of residents in low-quality residential environments, but we do not find above-average effects on socially weak groups. JEL Classification: R21, R31, Z32
CRIS-Team Scopus Importer:2022-04-15
Keywords: airbnb; gentrification; housing markets; Short-term rental